Unusual cutaneous features associated with a heterozygous gain‐of‐function mutation in IFIH1: overlap between Aicardi‐Goutières and Singleton‐Merten syndromes. (29th October 2015) - Bursztejn, A.‐C.; Briggs, T.A.; del Toro Duany, Y.; Anderson, B.H.; O'Sullivan, J.; Williams, S.G.; Bodemer, C.; Fraitag, S.; Gebhard, F.; Leheup, B.; Lemelle, I.; Oojageer, A.; et al.
Summary: Cutaneous lesions described as chilblain lupus occur in the context of familial chilblain lupus or Aicardi–Goutières syndrome. To date, seven genes related to Aicardi–Goutières syndrome have been described. The most recently described encodes the cytosolic double‐stranded RNA receptor IFIH1 (also known as MDA5), a key component of the antiviral type I interferon‐mediated innate immune response. Enhanced type I interferon signalling secondary to gain‐of‐function mutations in IFIH1 can result in a range of neuroinflammatory phenotypes including classical Aicardi–Goutières syndrome. It is of note that none of the patients with a neurological phenotype so far described with mutations in this gene was reported to demonstrate cutaneous involvement. We present a family segregating a heterozygous pathogenic mutation in IFIH1 showing dermatological involvement as a prominent feature, variably associated with neurological disturbance and premature tooth loss. All three affected individuals exhibited increased expression of interferon‐stimulated genes in whole blood, and the mutant protein resulted in enhanced interferon signalling in vitro, both in the basal state and following ligand stimulation. Our results further extend the phenotypic spectrum associated with mutations in IFIH1, indicating that the disease can be confined predominantly to the skin, while also highlighting phenotypic overlap with both Aicardi–Goutières syndrome and Singleton–Merten syndrome. Abstract : What's already known about this topic? Dermatological involvement is a major feature of the type I interferonopathies, which include the allelic disorders familial chilblain lupus (FCL) and Aicardi‐Goutières syndrome (AGS). Cutaneous lesions are seen in 40% of cases of AGS, but have never been described in the context of mutations in IFIH1 . What does this study add? IFIH1 mutations can be associated with predominant cutaneous features. This study highlights the overlap between AGS, FCL and Singleton–Merten syndrome, and emphasizes the utility of searching for an interferon signature as a diagnostic tool in this context. Linked Comment: Rutsch, Br J Dermatol 2015; 173: 1369–70 .